Corporate environmental reporting components and return on capital employed growth of the Nigerian listed manufacturing companies: An empirical analysis - Soetan, Timothy Adisa; Worimegbe, Powel Maxwell; Makinde, Olubisi Grace; Akintola, Abolade Francis; Adeoye, Solomon Olusegun (International Journal of Management and Sustainability, 2024)
This study explored the impact of corporate environmental reporting components on the growth of the return on capital employed in Nigerian listed manufacturing firms. The study adopted an ex post facto research design. 39 manufacturing businesses listed on the Nigeria Stock Exchange provided secondary data over the research period (2010-2109). The multiple regression statistical approach was used to analyse the data. This study made use of a quantitative research strategy. While environmental non-financial information did not show any significant influence on the return on capital employed growth of identified manufacturing organisations in Nigeria, results showed that environmental financial and performance information had a significant and beneficial impact. However, the data demonstrated that the integration of all aspects of corporate environmental reporting positively and statistically significantly influenced ROCE growth in Nigeria’s listed manufacturing businesses. A future study could expand the population of the study to include non-manufacturing companies in other industries. The implication of these results is that the manufacturing companies in Nigeria need to pay more attention to environmental, financial, and environmental performance information to enhance their return on capital employed growth. The writers were unable to locate any prior research that demonstrated this connection. Additionally, corporate environmental reporting components impact the growth of return on capital employed in listed manufacturing businesses in Nigeria, and this research provides new and significant findings in this area.